2002
DOI: 10.1021/ma020005b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfonated Polyimides as Polyelectrolytes for Fuel Cell Application. 1. Synthesis, Proton Conductivity, and Water Stability of Polyimides from 4,4‘-Diaminodiphenyl Ether-2,2‘-disulfonic Acid

Abstract: A sulfonated diamine monomer, 4,4‘-diaminodiphenyl ether-2,2‘-disulfonic acid (ODADS), was successfully synthesized by direct sulfonation of a commercially available diamine, 4,4‘-diaminodiphenyl ether (ODA), using fuming sulfuric acid as the sulfonating reagent. A series of sulfonated polyimides were prepared from 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA), ODADS, and common nonsulfonated diamines. The resulting sulfonated polyimides displayed much better stability toward water than those derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
363
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(373 citation statements)
references
References 12 publications
9
363
0
1
Order By: Relevance
“…21 The contact angle of a water droplet on the surface of a membrane provides the information about the outermost two or three monolayers of molecules on the surface. In this case it is determined by the presence of ionic or polar (which is -SO 3 K or -SO 3 (Fig.4) and 85.1 o to 73.3 o (Fig.5) respectively. Upon exposure to water, however, the contact angle dramatically decreases (by 5-18 o ) in a few seconds as the water droplet interacts strongly with the surface.…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
See 2 more Smart Citations
“…21 The contact angle of a water droplet on the surface of a membrane provides the information about the outermost two or three monolayers of molecules on the surface. In this case it is determined by the presence of ionic or polar (which is -SO 3 K or -SO 3 (Fig.4) and 85.1 o to 73.3 o (Fig.5) respectively. Upon exposure to water, however, the contact angle dramatically decreases (by 5-18 o ) in a few seconds as the water droplet interacts strongly with the surface.…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…Sulfonated derivatives of poly(ether sulfone) (SPES) [2], polyimide (SPI) [3], polyimidazole [4], polyphenylene [5], and polybenzimidazole [4] are among poly(aryl ether ketones) (PAEK) being investigated as PEM materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Aromatic polymers with sulfonic acid groups are promising materials for PEMs and polymer-inorganic hybrid membranes because of their outstanding thermal and chemical stability. Sulfonated derivatives of poly(ether sulfone) (SPES), [7][8][9] polyimide (SPI), [10][11][12] polyimidazole, 13 poly(aryl ether), 14,15 polyphenylene, 16,17 and polybenzimidazole 18 are among those being investigated as potential PEMs. However, to further simplify the preparation process and enhance performance of these materials, there are still some challenges, such as stereocontrollable chemical structures including easily controllable degree of sulfonation (DS) and sulfonation sites and well-refined microstructure by grafting, alternating, and blocking polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Mercier and co-workers reported the synthesis of a series of SPIs from 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA) and the results indicated that NTDA-based six-membered ring polyimides were more stable than five-membered ring PIs under fuel-cell conditions [15]. Okamoto and co-workers reported several series of SPIs based on sulfonated diamines and NTDA, some of which exhibited good fuel cell properties [22][23][24][25][26]. For example, sulfonated diamine monomers with flexible linkages, 4,4 ′ -diaminodiphenylether-2,2 ′ -disulfonic acid (ODADS) or 9,9-bis(4-aminophenyl)fluorene-2,7-disulfonic acid (BAPFDS) led to ODADS or BAPFDS-based polyimides that exhibited much better water stability than those derived from a widely used sulfonated diamine, 2,2 ′ -benzidinedisulfonic acid [23,24].…”
Section: Introductionmentioning
confidence: 99%